Pemanfaatan Panel Surya Berbasis Internet Of Things untuk Penyediaan Energi Pada Pemanas Air Listrik - Engla Desita; Endah Fitriani (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The use of renewable energy has become an essential solution to reduce dependence on limited fossil energy sources. Solar panels are an environmentally friendly alternative for generating electrical energy. This study develops a solar panel system based on the Internet of Things (IoT) to provide energy for electric water heaters. The system allows for the monitoring and control of energy usage through an IoT-based application, such as Telegram. The solar panels are connected to an ESP32-based controller system, which monitors sunlight intensity and battery charging status. The test results indicate that this system can provide sufficient energy for electric water heaters with optimal efficiency and reduce dependence on conventional energy sources.